Rapid Isolation and Identification of Pneumonia-Associated Pathogens from Sputum Samples Combining an Innovative Sample Preparation Strategy and Array-Based Detection - Pahlow, Susanne; Lehniger, Lydia; Hentschel, Stefanie; Seise, Barbara; Braun, Sascha D.; Ehricht, Ralf; Berg, Albrecht; Popp, Jürgen; Weber, Karina (ACS Omega, 2019)
With this study, an innovative and convenient enrichment and detection strategy for eight clinically relevant pneumonia pathogens, namely, Acinetobacter baumannii, Escherichia coli, Haemophilus influenzae, Klebsiella pneumoniae, Moraxella catarrhalis, Pseudomonas aeruginosa, Staphylococcus aureus, and Streptococcus pneumoniae is introduced. Bacteria were isolated from sputum samples with amine-modified particles exploiting pH-dependent electrostatic interactions between bacteria and the functionalized particle surface. Following this, an asymmetric polymerase chain reaction as well as subsequent stringent array-based hybridization with specific complementary capture probes were performed. Finally, results were visualized by an enzyme-induced silver nanoparticle deposition, providing stable endpoint signals and consequently an easy detection possibility. The assay was optimized using spiked samples of artificial sputum with different strains of the abovementioned bacterial species. Furthermore, actual patient sputum samples with S. pneumoniae were successfully analyzed. The presented approach offers great potential for the urgent need of a fast, specific, and reliable isolation and identification platform for important pneumonia pathogens, covering the complete process chain from sample preparation up to array-based detection within only 4 h.
CRIS-Team Scopus Importer:2023-04-20